AB-initio studies on properties of strain-free and strained perovskitetype (ABO3) multiferroic materials / Muhamad Kamil Yaakob - Yaakob, Muhamad Kamil (2015)
Multiferroic is one of the potential multifunctional materials for applications in novel based devices including magnetoelectric memory, spintronic and sensor. Efforts to develop more efficient multiferroic materials provide new opportunities and challenges in this field. Existing multiferroic materials were modified to enhance their existing properties. One of the known multiferroic materials is BiFeCb which has a great potential to exhibit excellent multiferroic properties at room temperature. In this work, the investigation focuses on the variety functional and physical properties of strain-free and strained perovskite-type multiferroic materials. The ab-initio calculations based on Density Functional Theory plus on-site Coulomb repulsion U method (LDA+U and GGA-PBEsol+U) as implemented in plane-wave pseudopotential CASTEP code were employed. The structural, lower energy symmetry, electronic, optical and elastic properties of strain-free BiFe03 were preliminary determined. It has been shown that the application of self-interaction corrected LDA+U and GGA-PBEsol+U functionals improve the accuracy of calculated properties. The results of structural, electronic, elastic and optical properties of BiFeCb, calculated using LDA+U and GGA-PBEsol+U are in good agreement with other available calculations and experimental data. The lower energy symmetry of strained BiFeCb was then studied via ab-initio calculation. The calculation revealed that the possible structural phase transformation discovered in strained BiFeCb is due to the difference in volumetric strain effects. Moreover, misfit strain effects on the structural phase transformation, morphotropic phase boundary and physical properties of epitaxial BiFeCb thin film were further investigated. The major finding in this study reveals that the coexistence of rhombohedral-like and tetragonallike phases in epitaxial BiFeC>3 thin film occurred at moderate compressive strain of inplane a-lattice parameter, which is also in excellent agreement with recent experimental studies. The optical blue shifted in monoclinic phase and red shifted inpure tetragonal phase of epitaxial BiFe03 thin film were also discovered. Additionally, the modified BiFe03 was investigated by substituting the Bi (III) with La (III). The rhombohedral to orthorhombic phase transformation in Bii-xLaxFe03 solid solution was determined at x= 0.57 for rhombohedral R3c and orthorhombic P21a phases respectively, which are consistent with available experimental and other calculation studies. Furthermore, the novel perovskite-type materials based on lone pair SbFeCb and BiVCb compounds were successfully designed in this work using ab-initio computational method. It has been found that the most stable crystal structure of SbFeCb is antiferromagnetic monoclinic Pc phase. For BiVC>3, ferromagnetic monoclinic P21/a phase (LaVCb-like structure) is found to be the most stable structure. These novel compounds have been found to demonstrate the structural phase transformation to polar monoclinic Pm and Cc phases under expansive volumetric strain effects. It is noted that the BiVC>3 and SbFe03 are metastable phase compounds under strain effect, which may be possible to be produced from high pressure-high temperature synthesis and epitaxial thin film growth techniques. Thus, the advanced epitaxial thin film growth technique is suggested as a potential method to synthesize BiV03 and SbFe03 single phase, which are promising candidates to be novel multiferroic materials.